Escape from highly effective public CD8+ T-cell clonotypes by HIV - Iglesias, Maria Candela; Almeida, Jorge R.; Fastenackels, Solène; van Bockel, David J.; Hashimoto, Masao; Venturi, Vanessa; Gostick, Emma; Urrutia, Alejandra; Wooldridge, Linda; Clement, Mathew; Gras, Stéphanie; Wilmann, Pascal G.; et al. (Blood, 2011)
Mapping the precise determinants of T-cell efficacy against viruses in humans is a public health priority with crucial implications for vaccine design. To inform this effort, we performed a comprehensive analysis of the effective CD8+ T-cell clonotypes that constitute responses specific for the HIV p24 Gag-derived KK10 epitope (KRWIILGLNK; residues 263-272) restricted by HLA-B*2705, which are known to confer superior control of viral replication in HIV-infected individuals. Particular KK10-specific CD8+ T-cell clonotypes, characterized by TRBV4-3/TRBJ1-3 gene rearrangements, were found to be preferentially selected in vivo and shared between individuals. These “public” clonotypes exhibit high levels of TCR avidity and Ag sensitivity, which impart functional advantages and enable effective suppression of HIV replication. The early L268M mutation at position 6 of the KK10 epitope enables the virus to avoid recognition by these highly effective CD8+ T-cell clonotypes. However, alternative clonotypes with variant reactivity provide flexibility within the overall KK10-specific response. These findings provide refined mechanistic insights into the workings of an effective CD8+ T-cell response against HIV.